The role of home medication storage location in increasing medication adherence for middle-aged and older adults - Gualtieri, Lisa; Shaveet, Eden; Estime, Brandon; Patel, Avi (Frontiers in Digital Health, 2022)
Background Over 50% of US adults do not take their prescriptions as prescribed, which is responsible for 33%–69% of hospital admissions and 125,000 deaths annually. Given the higher prevalence of prescription drug use among middle-aged and older adult populations, promoting medication adherence is of particular importance with these age groups. Two speculated facilitators of medication adherence are home medication storage location and the use of digital health devices. Objective Our objective was to use survey data to investigate the associations between medication storage location and medication adherence among adults 40 years and older. Additionally, we aimed to report preliminary findings about the associations between use of devices and medication adherence in this same population. Methods We conducted primary analysis of data sampled from a home medication management survey deployed in November 2021 (n = 580). We conducted exploratory analyses by way of chi2 tests and creation of bivariate logistic regression models. Results The most commonly used storage locations by our sample were nightstand drawers (27%), kitchen cabinets (25%), and atop bedroom nightstands (23%). Several medication storage locations were significantly associated with decreased odds of having ever forgotten to take a medication, including kitchen drawers, in refrigerators, atop bedroom nightstands, in nightstand drawers, and backpacks, purses, or bags. Two home medication storage locations were significantly associated with increased odds of having ever forgotten to take a medication: kitchen cabinets and bathroom vanities. Further, most (94%) survey respondents indicated they would be receptive to guidance about where to store their medications. Conclusions Given that some home medication storage locations are associated with adherence, an intervention to guide storage location selection may support increased adherence, especially with high receptivity expressed for such guidance. Increased adherence may also accrue from device usage paired with optimized home medication storage location. We plan to investigate that further, as well as how new device designs can incorporate contextual cues related to location to promote medication adherence more effectively in middle aged and older adults.